Nanoparticles for sunscreen and repair integration as well as preparation method and application of nanoparticles

By using nanoparticles of lipoic acid and sizuliolin, the shortcomings of existing sunscreens in sun protection and repair are solved, and efficient and safe bio-sunscreens are achieved, with excellent biocompatibility and antioxidant properties, which significantly improve the application value of the product.

CN119857061APending Publication Date: 2025-04-22WEST CHINA HOSPITAL SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510064822.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing sunscreens have shortcomings in sun protection and repair, chemical sunscreens can cause skin irritation and environmental pollution, while physical sunscreens have the disadvantages of heavy texture and clogging pores, and lack effective bio-sunscreen solutions.

Method used

Nanoparticles prepared with molar ratio of lipoic acid and sizuolin of (0.8-5): 1 were used to form nanoparticles by drying the melted blend of lipoic acid and sizuolin to achieve the integrated function of sun protection and repair.

Benefits of technology

The nanoparticles have excellent biocompatibility and antioxidant properties, can effectively absorb ultraviolet rays, enhance skin repair capabilities, and have sun protection, antioxidant and damage repair functions, which significantly improves the application value of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857061A_ABST
    Figure CN119857061A_ABST
Patent Text Reader

Abstract

The invention provides nanoparticles for sunscreen and repair integration as well as a preparation method and application of the nanoparticles, and belongs to the field of biomedical materials. The nanoparticle is prepared from lipoic acid and xanthoxylin as raw materials, and the molar ratio of the lipoic acid to the xanthoxylin is (0.8-5): 1. The nano-particles have excellent biocompatibility and oxidation resistance, can have excellent absorption capability on ultraviolet light, can effectively perform sun protection, and also have excellent after-sun repair capability. As a biological sun-screening agent, the biological sun-screening agent has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biomedical materials, and in particular relates to nanoparticles used for integrated sun protection and repair, and a preparation method and use thereof. Background Art

[0002] Ultraviolet (UV) radiation is the main exogenous factor causing skin photoaging and a variety of skin diseases. Traditional sunscreens mainly include chemical sunscreens and physical sunscreens. Chemical sunscreens (such as oxybenzone and avobenzone) protect the skin by absorbing ultraviolet rays, but they are prone to skin irritation and allergic reactions. At the same time, some chemical components may have adverse effects on the environment, such as damage to coral reefs. Physical sunscreens (such as titanium dioxide and zinc oxide) work by reflecting and scattering ultraviolet rays. Although they are less toxic, they often have disadvantages such as heavy texture, easy clogging of pores, and the appearance of a white film after application.

[0003] In recent years, biological sunscreens have gradually attracted attention due to their natural origin, high safety, and environmental friendliness. Biological sunscreens play a role in sun protection by removing or reducing oxygen-active group intermediates, blocking or slowing tissue damage, or promoting post-sun repair. They protect the skin from ultraviolet damage through antioxidant and repair mechanisms. It is very necessary to develop efficient and safe biological sunscreen materials that combine sun protection and repair functions.

[0004] Huajiao oil (HUA) is a natural active substance extracted from Sichuan pepper, which has excellent antioxidant capacity and UV absorption properties, and can effectively reduce UV-induced skin damage. Its structural formula is shown below:

[0005]

[0006] Lipoic acid (LA) is a natural short-chain fatty acid containing carboxyl groups and disulfide bonds synthesized by plants, animals and humans. It is biodegradable. As a natural antioxidant, LA has a unique hydrophobic-hydrophilic biphasic structure, and its structural formula is as follows:

[0007]

[0008] At present, there is no report on the combined use of xanthoxylum bungeol and lipoic acid to prepare a biological sunscreen for sun protection. Summary of the invention

[0009] In view of the problems existing in the prior art, the purpose of the present invention is to provide a nanoparticle for integrated sun protection and repair, and a preparation method and use thereof.

[0010] The invention provides a nanoparticle for integrated sun protection and repairing. The nanoparticle is prepared from lipoic acid and sanshinone as raw materials, and the molar ratio of lipoic acid to sanshinone is (0.8-5):1.

[0011] Furthermore, the molar ratio of lipoic acid to xinan is (1-2):1.

[0012] Furthermore, the molar ratio of lipoic acid to xanthoxylum bungeol is 2:1.

[0013] Furthermore, the nanoparticles are obtained by mixing and drying the melt of lipoic acid and xinan.

[0014] The present invention also provides a method for preparing the aforementioned nanoparticles, which comprises the following steps:

[0015] (1) heating lipoic acid to a molten state in a solvent;

[0016] (2) adding thioctic acid to the molten state of thioctic acid, and continuing the reaction until the thioctic acid is melted to obtain a molten blend of thioctic acid and thioctic acid;

[0017] (3) drying the melt blend obtained in step (2).

[0018] Further,

[0019] In step (1), the solvent is selected from anhydrous methanol, anhydrous ether or anhydrous ethanol;

[0020] And / or, in step (1), the concentration of lipoic acid is 50-300 mg / mL;

[0021] And / or, in step (1), the heating temperature is 50 to 130° C.; and / or, the heating time is 10 to 60 min;

[0022] And / or, in step (1), the rotation speed during heating is 100 to 1000 rpm.

[0023] Further,

[0024] In step (2), the reaction temperature is 50 to 130° C.; and / or the reaction time is 10 to 60 min;

[0025] and / or, in step (3), the temperature of the molten blend is reduced to 25-80° C. before drying;

[0026] And / or, in step (3), the drying is vacuum drying;

[0027] Preferably,

[0028] In step (3), the vacuum drying temperature is 25 to 80°C.

[0029] The present invention also provides use of the aforementioned nanoparticles in preparing biological sunscreens.

[0030] Furthermore, the nanoparticles are used for sun protection and repairing sunburned skin.

[0031] The present invention also provides a biological sunscreen, which is prepared using the aforementioned nanoparticles as active ingredients.

[0032] In the present invention, the "melt blend" refers to a mixture formed by mixing two or more raw materials (such as lipoic acid and zanthoxylum bungeanum) and then melting them together.

[0033] The present invention has achieved the following beneficial effects:

[0034] The present invention provides a novel sunscreen-repairing integrated nanoparticle, which utilizes the sulfur free radicals generated by lipoic acid in the ring-opening polymerization process to initiate the addition reaction between the carbon-carbon double bonds in zanthoxylum bungeanum and the physical combination to realize the reaction of zanthoxylum bungeanum and lipoic acid, thereby preparing a molten blend of zanthoxylum bungeanum and lipoic acid; then the molten blend is vacuum dried to remove the solvent, thereby forming a sunscreen-repairing integrated nanoparticle.

[0035] The nanoparticles of the present invention do not require multi-step synthesis of organic solvents during preparation, and are simple to operate and highly safe. The selected lipoic acid and thiamethoxam raw materials are cheap, easy to obtain, and have low cytotoxicity. In addition, thiamethoxam has excellent ultraviolet absorption capacity, and lipoic acid has strong antioxidant properties. The two can be used together to exert synergistic ultraviolet absorption capacity and antioxidant capacity, enhance skin repair ability, and have excellent sunscreen and light damage repair effects. Compared with traditional chemical or physical sunscreens, the nanoparticles of the present invention have sunscreen, antioxidant and damage repair functions. This comprehensive performance can significantly improve the application value of the product and meet the user's needs for safety, high efficiency and long-term effectiveness.

[0036] In summary, the nanoparticles of the present invention have excellent biocompatibility and antioxidant properties, can have excellent absorption capacity for ultraviolet light, can effectively protect against sunburn, and have excellent post-sun repair ability. The present invention has good application prospects as a biological sunscreen.

[0037] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0038] The above contents of the present invention are further described in detail below through specific implementation methods in the form of examples. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The infrared spectra (FT-IR) of raw materials, HUA, lipoic acid (LA), and nanoparticles prepared in Example 1 and Example 2.

[0040] Figure 2 The particle size results and SEM images of the nanoparticles prepared in Example 1 and Example 2.

[0041] Figure 3 The ultraviolet absorption spectra (UV-is) of raw materials, HUA, lipoic acid (LA), and nanoparticles prepared in Example 1 and Example 2.

[0042] Figure 4 The effects of raw material zanthoxylum bungeanum (HUA) and nanoparticles prepared in Example 1 and Example 2 on cell proliferation activity.

[0043] Figure 5 Cell live-death staining images of raw material zanthoxylum bungeanum (HUA) and nanoparticles prepared in Example 1 and Example 2.

[0044] Figure 6 The photoprotective effect of the nanoparticles prepared in Example 1 on cells irradiated with UVB.

[0045] Figure 7 The results show the effect of the nanoparticles prepared in Example 1 on the cell repair ability after sun exposure.

[0046] Figure 8 The gross image, HE staining image and Masson staining image of the rats irradiated with UVB after pretreatment with the nanoparticles prepared in Example 1.

[0047] Fig. 9 The following are the gross images, HE staining images and Masson staining images of sun-sunned rats after repairing them with the nanoparticles prepared in Example 1. DETAILED DESCRIPTION

[0048] The raw materials and equipment used in the present invention are all known products, which are obtained by purchasing commercially available products.

[0049] Example 1: Preparation of nanoparticles for integrated sun protection and repair according to the present invention

[0050] The method for preparing nanoparticles for integrated sun protection and repair of the present invention comprises the following steps:

[0051] Add anhydrous ethanol solution with a concentration of 50 mg / mL of lipoic acid to a clean reaction bottle, cover the lid, turn on the heating and stirring device, set the heating temperature to 60°C and the speed to 400 rpm, and heat for about 30 minutes to make the lipoic acid completely molten and break the disulfide bond; then slowly add 125 mg of prickly ash oil to make the molar ratio of lipoic acid to prickly ash oil 2:1, keep the reaction temperature at 60°C, fully react for 30 minutes, and after the reaction is completed, wait for the temperature to cool naturally to 25°C to obtain a molten blend. The obtained molten blend is placed in a vacuum drying oven, vacuum dried at 25°C for 2 hours to obtain nanoparticles, and placed at room temperature.

[0052] Example 2: Preparation of nanoparticles for integrated sun protection and repair according to the present invention

[0053] The method for preparing nanoparticles for integrated sun protection and repair of the present invention comprises the following steps:

[0054] Add anhydrous ethanol solution with a concentration of 50 mg / mL of lipoic acid to a clean reaction bottle, cover it, turn on the heating and stirring device, set the heating temperature to 60°C and the speed to 400 rpm, and heat for about 30 minutes to make the lipoic acid completely molten and break the disulfide bond; then slowly add 250 mg of prickly ash oil to make the molar ratio of lipoic acid and prickly ash oil 1:1, keep the reaction temperature at 60°C, and fully react for 30 minutes. After the reaction is completed, the temperature is naturally cooled to 25°C to obtain a molten blend. The obtained molten blend is placed in a vacuum drying oven, vacuum dried at 25°C for 2 hours to obtain nanoparticles, and placed at room temperature.

[0055] The beneficial effects of the present invention are demonstrated below through specific test examples.

[0056] Test Example 1: Evaluation of the physical and chemical properties of the nanoparticles used for integrated sunscreen and repair of the present invention

[0057] 1. Experimental Methods

[0058] 1. Grouping

[0059] The raw materials are zanthoxylum bungeanum (HUA), lipoic acid (LA), and the nanoparticles LAH (2:1) and LAH (1:1) prepared in Example 1 and Example 2.

[0060] 2. Detection method

[0061] HUA, LA, LAH(2:1) and LAH(1:1) were characterized by FT-IR and UV-Vis. The particle size of LAH(2:1) and LAH(1:1) was measured by nanoparticle size analyzer. The microstructure of LAH(2:1) and LAH(1:1) was observed by scanning electron microscopy (SEM).

[0062] 2. Experimental Results

[0063] Figure 1 The infrared spectrum (FT-IR) diagram of the nanoparticles prepared in Example 1 and Example 2. The strong absorption peak of pepper near ~1730cm-1 is a typical C=O (carbonyl) stretching vibration, which is the characteristic peak of pepper. Other absorption peaks near ~1600cm-1 may be related to the vibration of the aromatic ring C=C. The strong absorption peak of pure lipoic acid at ~1700cm-1 is the characteristic peak of C=O in lipoic acid. The absorption peak at ~1100-1200cm-1 is the stretching vibration of S=O (sulfur oxygen bond), indicating the existence of a unique functional group of lipoic acid. The absorption peak intensity and position of the LAH group at ~1730cm-1 and ~1700cm-1 change significantly. This may indicate that the carbonyl in HUA and the carbonyl in LA have some interaction (such as hydrogen bond or chemical bonding). The intensity of the S=O absorption peak at ~1100-1200cm-1 is weakened, which may be due to environmental changes or changes in some chemical bonds caused by the introduction of HUA. FT-IR results showed that lipoic acid and xanthocyanin were successfully combined.

[0064] Figure 2 The particle size and SEM image of the nanoparticles prepared in Example 1 and Example 2; the nanoparticles were dispersed in ultrapure water and ultrasonicated, and the particle size was measured using a nanoparticle size analyzer. The results showed that the particle size of LAH (1:1) was slightly larger, about 200nm; the particle size of LAH (2:1) was about 150nm. The microscopic morphology of the nanoparticles was observed using a scanning electron microscope (SEM). The nanoparticles were dispersed in anhydrous ethanol and ultrasonicated, and then dispersed on a mica sheet. The 3.0KV was used for observation, as shown in FIG. Figure 2 As shown, the particles are spherical and have uniform particle size distribution.

[0065] Figure 3The ultraviolet absorption spectrum (UV-is) of the nanoparticles prepared in Example 1 and Example 2. The nanoparticles were subjected to ultraviolet-visible spectroscopy analysis, and the pepper oil (HUA) showed an obvious absorption peak in the UVB region, and the absorption capacity was strong, indicating that it had a good shielding effect on UVB. The simple lipoic acid group (LA) had no absorption peak in the UVB range, indicating that LA had no ultraviolet absorption capacity, that is, a single lipoic acid did not have UVB protection ability and had no sunscreen effect. Compared with LA, the absorption of LAH (1: 1) and LAH (2: 1) in the UVB region was significantly enhanced, and the absorption peak at about 300nm was prominent, which showed that the nanoparticles of the present invention had a strong UVB absorption capacity.

[0066] Experimental Example 2: In vitro biological performance evaluation of the nanoparticles for integrated sunscreen and repair of the present invention 1. Experimental method

[0067] 1. Grouping

[0068] Raw material Zanthoxylum bungeanum (HUA), nanoparticles LAH (2:1) and LAH (1:1) prepared in Example 1 and Example 2.

[0069] 2. Cell proliferation

[0070] (1) Preparation of culture medium: After preparing complete culture medium, zanthoxylum bungeollin and nanoparticles prepared in Example 1 and Example 2 were added respectively to prepare culture medium with different drug concentrations (50, 100, 150, 200 μg / mL).

[0071] (2) Cell inoculation and treatment: Human immortalized keratinocytes (HaCaT) in the logarithmic growth phase were inoculated in a 96-well plate at 2000 cells / well. After sufficient adhesion, the culture medium containing different drugs was replaced and cultured for 24 hours. A control group was also set up in the experiment, and the cells were directly inoculated in the well plate and cultured normally.

[0072] (3) Cell activity detection: Cell proliferation activity was detected using a cell counting kit (CCK-8) 24 h after culture. A 10% (v / v) CCK-8 working solution was prepared using complete culture medium, the original culture medium in the test wells was removed, 200 μL of the working solution was added to each well, and the cells were incubated at 37°C for 2 h in the dark, and the absorbance was measured at 450 nm.

[0073] 3. Cell activity

[0074] (1) Cell inoculation: HaCaT cells in logarithmic growth phase were inoculated into 24-well plates at 20,000 cells / well. After sufficient adhesion, the culture medium containing 100 μg / mL xinan oil, the nanoparticles prepared in Example 1 or the nanoparticles prepared in Example 2 was added and culture was continued for 24 hours.

[0075] (2) Preparation of working solution: Add 5 μL of propidium iodide (PI) and calcein to 5 mL of DMEM high-glucose medium to prepare the live-dead staining working solution.

[0076] (3) Live-death staining: After culturing HaCaT for 24 h, the culture medium was removed and the cells were washed with PBS. 500 μL of live-death staining working solution was added to each well and incubated at 37°C in the dark for 15 min. The live-death status of the cells was observed using a confocal microscope and images were collected.

[0077] 2. Experimental Results

[0078] CCK8 experimental results ( Figure 4 ) showed that after 24 hours of culture with each group of drugs, the cells in each group still maintained good proliferation activity, and the cell proliferation activity was better when the concentration was less than 150μg / mL. Cell survival results ( Figure 5 ) showed that the cells in each group survived well, and no dead cells were found. The above experimental results show that the nanoparticles prepared by the present invention have good biocompatibility.

[0079] Experimental Example 3: Evaluation of the UV absorption capacity of cells by the nanoparticles used for integrated sun protection and repair of the present invention

[0080] 1. Experimental Methods

[0081] The UV absorption ability of the nanoparticles prepared in Example 1 was evaluated.

[0082] 1. Grouping

[0083] Raw material: Zanthoxylum bungeanum (HUA) and nanoparticles LAH prepared in Example 1.

[0084] 2. DCFH-DA evaluates intracellular ROS levels

[0085] (1) Construction of cell sunscreen model: HaCaT cells in logarithmic growth phase were seeded in 6-well plates at 50,000 cells / well. After sufficient adhesion, culture medium of each group (HUA or LAH dissolved in complete culture medium at a concentration of 100 μg / mL) was added and culture was continued. Immediately after adding the culture medium, the cells were heated at 1000 μW cm -2 The cells were irradiated for 100 seconds at a high UV intensity and cultured for 12 hours. The Blank group and UVB group were set up separately. The cells in the Blank group were directly inoculated in the well plate and cultured normally without adding drugs or UVB irradiation. The cells in the UVB group were inoculated in the well plate and cultured without adding drugs but only UVB irradiation.

[0086] (2) DCFH-DA staining: 100 μL DCFH-DA dye was added to 20 mL high-glucose culture medium to obtain a working solution. After culture, cells from each group were collected, and the prepared working solution was added and incubated for 15 minutes; after washing with PBS, the cells were detected by flow cytometry.

[0087] 2. Experimental Results

[0088] Figure 6 is the intracellular ROS level of each treatment group. Under ultraviolet stimulation, excessive production of ROS will occur, which will trigger oxidative stress response and directly lead to cell damage. The results showed that the ROS level in the UVB group increased significantly compared with the Blank group, while the ROS level in the HUA and LAH groups decreased significantly. Among them, the ROS expression level in the LAH group was significantly lower than that in the HUA group, and even lower than that in the Blank group. The experimental results show that the nanoparticles prepared by the present invention can significantly reduce the ROS produced by UVB and have excellent antioxidant capacity. In addition, studies have shown that the nanoparticles of the present invention obtained by combining lipoic acid and prickly ash can synergistically inhibit ROS expression, and the anti-ultraviolet damage effect is significantly better than the use of prickly ash and lipoic acid alone, and the sunscreen effect is excellent.

[0089] Experimental Example 4: Evaluation of the post-sun repair ability of the nanoparticles used for integrated sun protection and repair of the present invention on cells

[0090] 1. Experimental Methods

[0091] The after-sun repair ability of the nanoparticles prepared in Example 1 was characterized.

[0092] 1. Grouping

[0093] Raw material: Zanthoxylum bungeanum (HUA) and nanoparticles LAH prepared in Example 1.

[0094] 2. Flow cytometry to assess cell apoptosis

[0095] (1) Construction of cell sunscreen model: HaCaT cells in logarithmic growth phase were seeded in 6-well plates at 50,000 cells / well. After fully adhering to the plate, the cells were heated at 1000 μW cm -2 Irradiation was performed for 100 seconds at a high UV intensity. Immediately after irradiation, the culture medium of each group was replaced (HUA or LAH was dissolved in complete culture medium at a concentration of 100 μg / mL) and cultured for 12 hours. The Blank group and UVB group were set up separately. The cells in the Blank group were directly inoculated in the well plate and cultured normally without UVB irradiation or drug addition. The cells in the UVB group were inoculated in the well plate and cultured, and only UVB was irradiated without drug addition.

[0096] (2) FITC / PI staining: Add 5 μL FITC dye to 200 μL PBS to obtain a working solution. Collect cells from each group, add the prepared working solution and incubate for 5 minutes; then add 5 μL PI dye and detect by flow cytometry.

[0097] 2. Experimental Results

[0098] Figure 7 is the level of cell apoptosis in each group. Ultraviolet irradiation can stimulate excessive ROS production, which directly leads to cell senescence. The results show that the proportion of cell apoptosis in the UVB group increased significantly compared with the Blank group, and there were relatively more late apoptotic cells; the level of cell apoptosis in the HUA group was particularly high, indicating that zanthoxylum bungeanum would cause secondary damage to cells after sun exposure; the LAH group decreased significantly compared with the UVB group and the HUA group, especially the late apoptotic cell population; this shows that the addition of lipoic acid can greatly improve the biocompatibility and anti-apoptosis ability of zanthoxylum bungeanum. Studies have shown that zanthoxylum bungeanum and lipoic acid in the nanoparticles prepared by the present invention can synergistically inhibit cell apoptosis caused by UVB, and have excellent post-sun repair ability.

[0099] Experimental Example 5: Animal Experimental Evaluation of UV Absorption Capacity of Nanoparticles for Integrated Sunscreen and Repair of the Present Invention

[0100] 1. Experimental Methods

[0101] The nanoparticles prepared in Example 1 were evaluated for their ability to protect against skin sunburn in vivo.

[0102] 1. Grouping

[0103] Raw material: Zanthoxylum bungeanum (HUA) and nanoparticles LAH prepared in Example 1.

[0104] 2. Construction of Rat Sunscreen Model

[0105] The experimental animals in this test case were all male SD rats weighing 250±5g. The rats were depilated in an area of ​​about 2.5×2.5cm on their backs. The experiment was divided into 4 groups: Blank group, UVB group, HUA group, and LAH group. The depilatory area in the Blank group was not treated with any treatment. The other three groups of rats were pretreated with materials in the depilatory area every day and then exposed to 1000μWcm -2 Irradiation was performed for 300 seconds at the highest UV intensity for 5 consecutive days.

[0106] The material pretreatment methods are as follows:

[0107] The UVB group was exposed directly to UV light without material pretreatment;

[0108] The pretreatment method for the HUA group was to dissolve HUA and xanthocollagen in 1 mL of deionized water at a mass ratio of 1:1 (50 mg each) and then apply it to the hair removal area;

[0109] The pretreatment method for the LAH group was to dissolve LAH and xanthocollagen in 1 mL of deionized water at a mass ratio of 1:1 (50 mg each) and then apply it to the hair removal area.

[0110] 2. Experimental Results

[0111] Figure 8 The different material groups were sampled for gross observation, HE and Masson staining. From the perspective of skin appearance, the Blank group had smooth and intact skin without damage; the UVB group showed obvious skin scabs and was dry; the HUA group also had a small amount of skin scabs, but compared with the UVB group, the skin damage gradually decreased, and the skin appearance of the LAH group was close to normal, indicating that it had a significant protective effect against UV damage. Secondly, through HE staining analysis, the UVB group showed disordered epidermal structure, loose cell arrangement, and obvious inflammatory cell infiltration, while the HUA group and LAH group gradually restored normal epidermal structure, among which the epidermis of the LAH group was intact, the cells were tightly arranged, and there was almost no inflammatory infiltration. In addition, the results of Masson staining showed that the collagen fibers in the dermis of the UVB group were sparse and severely damaged, while the collagen fibers in the HUA group gradually increased and were tightly distributed, and the collagen fiber network in the LAH group was close to the level of normal skin. Lipoic acid itself has no UV absorption effect and does not have a sunscreen effect. The nanoparticles prepared from zanthoxylum bungeanum and lipoic acid can exert a synergistic UV protection effect and have an excellent protective effect against UV damage.

[0112] Experimental Example 6: Animal experiment to evaluate the after-sun repair ability of the nanoparticles used for integrated sun protection and repair of the present invention

[0113] 1. Experimental Methods

[0114] The nanoparticles prepared in Example 1 were evaluated for their ability to repair after sun exposure in vivo.

[0115] 1. Grouping

[0116] Raw material: Zanthoxylum bungeanum (HUA) and nanoparticles LAH prepared in Example 1.

[0117] 2. Construction of rat sun damage model:

[0118] The experimental animals in this experiment were all male SD rats weighing 250±5g. The rats were depilated in an area of ​​about 2.5×2.5cm on their backs. The experiment was divided into 4 groups: Blank group, UVB group, HUA group and LAH group. The depilated area in the Blank group was not treated in any way. The UVB group was exposed to 1000μWcm -2 UVB irradiation was performed for 300 seconds in the HUA and LAH groups at 1000 μW cm -2 After 300 seconds of UVB irradiation, each group of materials was applied for 5 consecutive days.

[0119] Here are the methods for applying various materials:

[0120] In the HUA group, HUA and xanthocollagen were dissolved in 1 mL of deionized water at a mass ratio of 1:1 (50 mg each) and then applied to the hair removal area;

[0121] In the LAH group, LAH and xanthocollagen were dissolved in 1 mL of deionized water at a mass ratio of 1:1 (50 mg each) and then applied to the hair removal area.

[0122] 2. Experimental Results

[0123] Fig. 9 The skin of the different repair materials was observed and HE and Masson staining were performed. In terms of appearance changes, the skin of the Blank group was smooth and intact without any damage. The skin of the UVB group was obviously damaged, showing dullness, dryness and inflammatory reaction, with spots or ulcers, indicating that ultraviolet rays caused significant damage. The degree of skin damage in the HUA group was alleviated, but some dryness and inflammatory reaction were still visible, and the repair effect was limited. The skin appearance of the LAH group was close to that of the Blank group, and the damage was basically gone, showing a good repair ability. HE staining results showed that the epidermal cells in the UVB group were disordered, inflammatory cells were significantly infiltrated, and the dermis was severely damaged. The cell arrangement in the HUA group was slightly restored, and the inflammatory reaction was alleviated, but it did not reach the level of complete repair. The epidermal cell structure of the LAH group was restored intact, and the inflammatory cells basically disappeared, close to the normal state of the Blank group. Masson staining analysis found that the collagen fibers in the UVB group were reduced and disordered, and the dermis structure was severely damaged. The fibrils in the HUA group were restored, but the density and arrangement were still lower than those in the Blank group. The density and arrangement of the fibrils in the LAH group tended to be normal, showing its significant effect in the reconstruction of collagen fibers. The LAH group showed the best effect in the repair of ultraviolet damage, not only effectively relieving the inflammatory response, but also significantly promoting the recovery of the epidermal structure and the regeneration of collagen fibers, showing its potential in after-sun repair. The present study shows that thunbergii oil and lipoic acid can play a synergistic role in after-sun repair.

[0124] In summary, the present invention provides a nanoparticle for integrated sunscreen and repair. The nanoparticle is prepared by melt blending of sanshool and lipoic acid. The nanoparticle has excellent biocompatibility and antioxidant properties, can have excellent absorption capacity for ultraviolet light, can effectively protect against the sun, and has excellent after-sun repair ability. The present invention has good application prospects as a biological sunscreen.

Claims

1. A nanoparticle for integrated sun protection and repair, characterized in that: The invention is prepared from lipoic acid and santheme oil as raw materials, and the molar ratio of lipoic acid to santheme oil is (0.8-5):

1.

2. The nanoparticle according to claim 1, characterized in that: The molar ratio of lipoic acid to xinan is (1-2):

1.

3. The nanoparticle according to claim 2, characterized in that: The molar ratio of lipoic acid to xinan is 2:

1.

4. The nanoparticle according to any one of claims 1 to 3, characterized in that: The nanoparticles are obtained by mixing thioctic acid and fennel molten material and then drying them.

5. A method for preparing the nanoparticles according to any one of claims 1 to 4, characterized in that: It includes the following steps: (1) heating lipoic acid to a molten state in a solvent; (2) adding thioctic acid to the molten state of thioctic acid, and continuing the reaction until the thioctic acid is melted to obtain a molten blend of thioctic acid and thioctic acid; (3) drying the melt blend obtained in step (2).

6. The method according to claim 5, characterized in that: In step (1), the solvent is selected from anhydrous methanol, anhydrous ether or anhydrous ethanol; And / or, in step (1), the concentration of lipoic acid is 50-300 mg / mL; And / or, in step (1), the heating temperature is 50 to 130° C.; and / or, the heating time is 10 to 60 min; And / or, in step (1), the rotation speed during heating is 100 to 1000 rpm.

7. The method according to claim 5, characterized in that: In step (2), the reaction temperature is 50 to 130° C.; and / or the reaction time is 10 to 60 min; and / or, in step (3), the temperature of the molten blend is reduced to 25-80° C. before drying; And / or, in step (3), the drying is vacuum drying; Preferably, In step (3), the vacuum drying temperature is 25 to 80°C.

8. Use of the nanoparticles according to any one of claims 1 to 4 in the preparation of biological sunscreens.

9. The use according to claim 8, characterized in that: The nanoparticles are used for sun protection and repairing sunburned skin.

10. A biological sunscreen, characterized in that: The nanoparticles are prepared by taking the nanoparticles described in any one of claims 1 to 4 as active ingredients.